Speech delivered by Dr Luis M Bosch del Marco in the tribute session to Dr Emilio A Bonnecarrère held on November 6, 1963 - Bosch del Marco, Luis M (Cirugía del Uruguay, 2020)
Presented at session 6th November 1963